2021
DOI: 10.3390/rs13183669
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Classification and Accuracy Assessment from High-Resolution Images of Coastal Wetlands

Abstract: High-resolution images obtained by multispectral cameras mounted on Unmanned Aerial Vehicles (UAVs) are helping to capture the heterogeneity of the environment in images that can be discretized in categories during a classification process. Currently, there is an increasing use of supervised machine learning (ML) classifiers to retrieve accurate results using scarce datasets with samples with non-linear relationships. We compared the accuracies of two ML classifiers using a pixel and object analysis approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…For example, Samiappan et al [18] reported that when using the OBIA method based on UAV for coastal wetland mapping, extensive time and effort were spent in the selection of image segmentation parameters. In addition, Martínez Prentice et al [27] revealed that the PB method is more accurate than the OBIA method when monitoring coastal wetland vegetation based on UAV and suggested that the result of the PB method is more reflective of the distribution of vegetation in coastal wetlands with high landscape heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Samiappan et al [18] reported that when using the OBIA method based on UAV for coastal wetland mapping, extensive time and effort were spent in the selection of image segmentation parameters. In addition, Martínez Prentice et al [27] revealed that the PB method is more accurate than the OBIA method when monitoring coastal wetland vegetation based on UAV and suggested that the result of the PB method is more reflective of the distribution of vegetation in coastal wetlands with high landscape heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, almost no studies have evaluated the classification performance of the three paradigms, PB, OBIA, and DL, in coastal wetland UAV data. Since the PB and OBIA methods are the most common paradigm for UAV data processing in coastal wetlands [15,16,27] and are mutually independent of DL methods in processing and analysis, an understanding of the paradigm shift between them would be more practical and essential for coastal wetland monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel-2 data have been widely used to map different habitats and several studies have demonstrated their reliability in mapping and monitoring changes in marine biocenoses such as coral (Hedley et al 2012 ), mangrove (Pham et al 2019b , 2020 ) and seagrass beds Topouzelis et al 2016 ; Traganos and Reinartz 2018b ; Ha et al 2020 , 2021 ; Wicaksono et al 2021 ; Nur et al 2021 ; Ivajnšič et al 2022 ; Hartoni et al 2022 ). Many authors have used vegetation indices as the input for RF classification to map plant communities in terrestrial wetlands (Fletcher 2016 ) and coastal wetlands (Zoffoli et al 2020 ; Martínez Prentice et al 2021 ; Benmokhtar et al 2021 ), and compared to many machine learning algorithms and support vector machine techniques, the RF algorithm has produced promising results in terms of classifying seagrass (Zhang et al 2013 ; Traganos and Reinartz 2018b ; Ha et al 2020 ). For example, to monitor the dynamics of the Posidonia oceanica (L.) Delile meadows and Cymodocea nodosa (Ucria) Ascherson meadows in the Eastern Mediterranean, Traganos and Reinartz ( 2018a ) used the random forest algorithm and support vector machines for the RapidEye time series, after adjusting the atmospheric and analytical water column.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial resolution of satellite imagery is sometimes inadequate to capture the spectral characteristics of the spatially variable vegetation types (Singhal et al, 2019). Thus, high-resolution unmanned aerial vehicles (UAVs) are gaining popularity among geospatial scientists, who recognize the benefits of their spectral information for spotting minute features (Martínez Prentice et al, 2021).…”
Section: Introductionmentioning
confidence: 99%